2014
DOI: 10.1159/000360766
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics of Cardiovascular Disease: A New ‘Beat' in Coronary Artery Disease

Abstract: Genome-wide association studies have become a powerful tool in the identification of disease-associated variants. Unfortunately, many of these studies have found that the estimated variability in cardiovascular disease (CVD) risk cannot be fully explained by traditional paradigms of genetic variation in protein-coding genes. Moreover, traditional views do not sufficiently explain the well-known link between CVD and environmental influence. We posit that epigenetics, defined as chromatin-based mechanisms import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 126 publications
0
39
0
Order By: Relevance
“…During endothelial dysfunction, these properties are lost and endothelial cells (ECs) promote vascular disease development. 1,2 Understanding the fundamental mechanisms governing endothelial phenotype switching offers novel approaches to prevent and alter the course of vascular disease. Epigenetic mechanisms conserve the cellular identity and give rise to developmental processes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…During endothelial dysfunction, these properties are lost and endothelial cells (ECs) promote vascular disease development. 1,2 Understanding the fundamental mechanisms governing endothelial phenotype switching offers novel approaches to prevent and alter the course of vascular disease. Epigenetic mechanisms conserve the cellular identity and give rise to developmental processes.…”
mentioning
confidence: 99%
“…The epigenetic control of EC biology, however, is incompletely understood. [2][3][4] Histone methylation is an important mechanism of epigenetic regulation. Trimethylation at histone 3 lysine 4 (H3K4me3), located in promoter regions, is associated with gene expression.…”
mentioning
confidence: 99%
“…15 However, unlike the well-studied microRNAs, the knowledge on lncRNAs is still at a premature stage. 5,9,14 The lncRNAs are pervasively abundant and important for cells in every branch of organisms. They can be found in both the nucleus and cytoplasm.…”
Section: Physiology and Function Of Lncrnasmentioning
confidence: 99%
“…2 Apart from the traditional and environmental risk factors for cardiometabolic diseases, including diabetes, dyslipidemia, hypertension and obesity, human genome variance is involved in the disease development. 5 To improve understanding of cardiometabolic disease pathogenesis, large efforts employing genome-wide association studies (GWAS) have identified numerous disease-associated singlenucleotide polymorphisms (SNPs). Most of them are enriched within noncoding elements, and very few of them are found in the coding that allows reasoning by the difference in structural change of the protein.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation